Activated carbon in mixed-matrix membranes. Issue 1 (2nd January 2021) - Lewis, Jeremy; Al-sayaghi, Maram A. Q.; Buelke, Chris; Alshami, Ali
Abstract : Mixed matrix membranes (MMMs) have emerged as strong contenders to conventional membranes for gas and liquid separations. Although numerous studies on filler/matrix combinations have been conducted and thoroughly reviewed, a review of activated carbon (AC) as a filler has thus far been minimal. This review intends to fill this gap via critically analyzing the state-of-the-art on AC as a filler in MMMs. Aspects of AC-MMM research, with emphasis on AC fabrication from biomass pyrolysis, AC-MMM fabrication and resulting properties, and influence of AC on MMM performance are thoroughly elucidated. Furthermore, the various applications that have been investigated with AC-MMM membranes, and several predictive models that have been specifically utilized for AC-MMMs are also discussed.